âValues, Challenges, and Critical Success Factorsâ of Building Information Modelling (BIM) in Malaysia: Experts Perspective - Al-Ashmori, Y.Y. (MDPI, 2022)
Building Information Modelling (BIM) plays a major role in enhancing the building project process. However, BIM implementation in building projects has not been categorized, and no previous investigation of its value in the different building project types has been undertaken. This research intended to evaluate BIM implementation in building projects and to identify its values, challenges, and enablers. Experts from BIM consultancy organizations were the respondents in this study. Based on nine interviews and 26 responses to a structured questionnaire, a quantitative approach to the content validity method was adopted. The results reveal that BIM implementation in mid-and low-rise buildings is very low. Only top organizations are able to implement BIM in their projects. Experts suggested that local organizations are not able to implement BIM due to their inability to adopt the BIM system as a digital management process throughout the project life cycle. In addition, there was consensus agreement based on the Content Validity Ratio (CVR) that BIM adds significant value to building projects, which includes providing collaborative organizations, greater communication, increased client satisfaction, more cost-savings, increased productivity, and a new way of reasoning for projects. This research also identified 20 challenges and 45 enablers of BIM implementation in mid-and low-rise building construction by the local firms. From the result, it was found that the presented variables were reliable, as reported in the interview transcripts and based on the majority of expertsâ opinions. This research provides an important list of challenges and success factors that need to be considered to overcome the critical issue of low BIM implementation in building projects. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.